Prescribing Mental Health Medication - Doran Christopher M (Routledge - Taylor & Francis Group, 2003)
This book is a must add to any practicing physician's set of in office clinical references.The author provides pragmatic, well researched guidance coupled with loads of practical suggestions for ways to talk with patients and improve the effectiveness of treatment. Preface, Ackowledgements, The Need for This book, General Principles of Medication Management, Myths and Truths about Mental Health Medication, Medication Management Start to Finish, Helping a Patient to Try Medication, Starting Medication, FollowUp Appointmrnts and Strategies, Medication and Psychotherapy, Stopping Medication, The Long Term Patient, Medicating Special Population, Using Medication with Children and Adolesents, Pregnancy and Psychotropics Rewards and Risks, Prescribing Psychotropics for Older Patients, Medication of Sleep Problems, Alcohol and Mental Health Medications, The Confused and Cognitively Impaired Patient Medication Pitfalls, Medication Dillemmas and Their Clinical Management, Psychotropics Medicationsand Side Effects, Danger Zones Areas of Risk Psychotropics, Medication Allergies, Competent Clinical Practice, Prescription Writing and Record Keeping, Serum Blood of Psychotropics, General Medications, Keeping Current, Appendices, Index.